Innovative Weed Control Technologies in Oil Palm Circles: Evaluating Effectiveness and Cost Efficiency at the Immature Phase - Heru Wansyah Harahap; Hartini Hartini (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Weeds become major constraint in oil palm plantations as they compete for nutrients, light, and water, thereby extending the non-productive period. This study aimed to evaluate the effectiveness of weed control methods on the dominant weed species in the immature oil palm plants (TBM). The research was conducted at Johan Sentosa Estate, PT Agrinas Palma Nusantara, using a Randomized Block Design with three treatments and 10 replications. The treatments involved A (450 mL/ha glyphosate + 22.7 g/ha metsulfuron-methyl), B (manual weeding), and C (450 mL/ha paraquat + 22.7 g/ha metsulfuron-methyl). Observation included weed mortality, regrowth, phytotoxicity, and operational cost. Data was analyzed using Kruskal–Wallis and Mann–Whitney tests at a 5% significance level. Results showed significant differences among treatments (p < 0.05) with manual weeding (B) achieved the highest weed mortality in the early observation (mean rank = 15.50) but incurred the highest annual cost 589,621.45 IDR/ha. Treatmant A provided the most effective suppression of weed regrowth up to the 8th week (mean rank = 15.50) with annual cost 355,056.61 IDR/ha, and treatment C showed comparable effectiveness to A but a lower cost 339,397.25 IDR/ha. None of the treatments caused phytotoxicity symptoms (score 0) on oil palm plants. The treatment A using glyphosate and metsulfuron-methyl was identified as the most effective and cost-efficient weed control method for immature oil palm circles.